MISTAKES AND COMPLICATIONS AFTER SURGICAL TREATMENT OF LUMBAR SPONDYLOLISTHESIS. CLINICAL CASE - Chernyshov, Olexandr; Golbaum, Maksym (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Spondylolisthesis is a pathology of the musculoskeletal system that causes a vertebra to move forward, sideways or backward. Most often, it is treated surgically using transpedicular structures. Objective. To present a clinical case of re-treatment for degenerative lumbar spondylolysis of the LV vertebral body using transpedicular and posterior autografting techniques. Methods. The clinical case of lumbar spine osteochondrosis, spondyloarthritis, posterior transpedicular fusion LV–SI, fracture of the screw in the body of the SI vertebra on the right, and spinal canal stenosis at the level of LV–SI is described. Lower paraparesis. Results. The patient underwent metal removal, decompression of the spinal canal at the level of LV–SI, open reduction of the LV vertebral body, posterior transpedicular fusion of LIV–SI and posterior autografting fusion. The surgical intervention was successful, despite the technical difficulties associated with removing the threaded part of the broken screw. According to the visual analogue scale, the patient had 8 points before the operation, which indicates acute pain syndrome, and after that the pain intensity decreased to 4 points. Muscle strength of the right and left lower extremities before surgery was 2 and 2.5 points, respectively, 5 days after surgery, improvement was recorded — 3 points for each limb. From the second day after repeated surgical treatment, the patient showed a significant improvement in muscle sensitivity and strength in both lower extremities. Conclusions. The clinical example of repeated surgery due to the failure of the metal structure and the deterioration of the patient’s neurological status highlights the need for postoperative follow-up. Taking into account the percentage of complications after transpedicular spondylodesis, it is necessary to continue scientific research to improve the results of surgical treatment of patients with degenerative diseases of the spine.